2006
DOI: 10.1242/dev.02385
|View full text |Cite
|
Sign up to set email alerts
|

VEGF activates divergent intracellular signaling components to regulate retinal progenitor cell proliferation and neuronal differentiation

Abstract: During vertebrate neurogenesis, multiple extracellular signals influence progenitor cell fate choices. The process by which uncommitted progenitor cells interpret and integrate signals is not well understood. We demonstrate here that in the avascular chicken retina, vascular endothelial growth factor (VEGF) secreted by postmitotic neurons acts through the FLK1 receptor present on progenitor cells to influence cell proliferation and commitment. Augmenting VEGF signals increases progenitor cell proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 85 publications
8
96
0
Order By: Relevance
“…For example, neuromodulators such as cannabinoids, opioid, NPYas well as the mood stabilizer valproate increase neurogenesis via a MAPK-dependent mechanism (Hao et al, 2004;Howell et al, 2005;Jiang et al, 2005;Persson et al, 2003;Reuda et al, 2002). Furthermore, vascular endothelial growth factor-mediated proliferation of retinal progenitor cells is also dependent on MAPK signaling (Hashimoto et al, 2006), and using a slice culture technique, MAPK signaling has been shown to stimulate hypoxiainduced neurogenesis (Zhou and Miller, 2006;Zhou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, neuromodulators such as cannabinoids, opioid, NPYas well as the mood stabilizer valproate increase neurogenesis via a MAPK-dependent mechanism (Hao et al, 2004;Howell et al, 2005;Jiang et al, 2005;Persson et al, 2003;Reuda et al, 2002). Furthermore, vascular endothelial growth factor-mediated proliferation of retinal progenitor cells is also dependent on MAPK signaling (Hashimoto et al, 2006), and using a slice culture technique, MAPK signaling has been shown to stimulate hypoxiainduced neurogenesis (Zhou and Miller, 2006;Zhou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In adults, expression is generally restricted to the inner nuclear layer (MĂŒller cells and amacrine cells), the ganglion cell layer, and the retinal vasculature (Stitt et al, 1998). However, during retinal neurogenesis VEGFR-2 is also expressed by neural progenitor cells (Hashimoto et al, 2006). Notably, neural cell VEGFR-2 can be activated by VEGF in vitro (Yang et al, 1996).…”
Section: Retinal Expression Of Vegf and Vegfrmentioning
confidence: 99%
“…Similarly, conditional ablation of Shh and Smoothened (Smo) in mice results in Atoh7-dependent overproduction of RGCs (Sakagami et al, 2009). VEGF (vascular endothelial growth factor) is also secreted by RGCs and other postmitotic neurons and can negatively regulate RGC differentiation (Hashimoto et al, 2006). Thus, RGC formation is reduced by enhanced VEGF signals but increased by disrupting VEGF signaling activity (Hashimoto et al, 2006).…”
Section: Extrinsic Signalingmentioning
confidence: 99%